Soil Drenching and Foliar Application of Nano Fertilizers Improved Quality Traits and Vase Life of Asparagus densiflorus cv. ‘Sprengeri’ - Sri, M. Sathya; Kumar, S.; Shricharan, Senthilkumar (International Journal of Economic Plants, 2025)
The current study was carried out during September, 2022 to March, 2023 at Chidambaram, Cuddalore District, Tamil Nadu, India. The study examined the impact on enhancing quality and marketability, responding to the urgent demand for sustainable fertilization methods. Asparagus densiflorus cv. Sprengeri was a valued ornamental foliage plant, extensively utilised in flower arrangements for its vibrant green leaves and outstanding vase longevity. Nano fertilizers are used as an alternative to conventional fertilizer for its gradual and controlled supply of nutrients in the soil. They could release their active ingredients more precisely in response to environmental cues and biological demands, enhancing soil health by increasing carbon uptake, soil aggregation, water holding capacity, and crop nutrient usage efficiency. The experiment was laid out in a completely randomized design with three replications, incorporating 12 treatments that included nano NPK 4:4:4 soil drenches (1500 ppm, 3000 ppm and 4500 ppm) and Nano urea foliar sprays (0.05% and 0.1%), with a control (water spray). The application of nano NPK 4:4:4 soil drenches at 4500 ppm+nano urea foliar spray at 0.1% markedly enhanced visual scoring, freshness index, chlorophyll content, and vase life, followed by Nano NPK 4:4:4 soil drenches @ 4500 ppm + nano urea foliar spray @ 0.05 %. The lowest values were recorded with control, indicating the enhanced nutrient efficiency and physiological advantages of nano fertilizers. These results highlighted the capacity of nano fertilizers to improve crop quality, mitigate impacts on the environment, and promote economic feasibility.